PENGARUH EKSTRAK DAUN BIDARA DAN DAUN GINSENG JAWA TERHADAP GAMBARAN MAKROSKOPIK GINJAL JANTUNG DAN HATI TIKUS HIPERTENSI - Yuliana, Dewi; Syuhada, Anugerah Putri; Syam, Andi Suci Alfira; Putri, Nurlaila; Aulia, Vivi; Ang, Dynasti Kelani; Emelda, Andi (As-Syifaa Jurnal Farmasi, 2025)
Hypertension, or high blood pressure, is a condition characterized by a sustained increase in blood pressure, exceeding the normal value of ≥140/90 mmHg. Hypertension therapy aims to lower both systolic and diastolic blood pressure to restore normal levels and minimize the risk of complications. The use of herbal plants such as bidara leaves (Ziziphus mauritiana L.) and Javanese ginseng (Talinum paniculatum (Jacq.) Gaertn.) holds potential as an alternative in the management of hypertension. Medicinal plants and plant-derived compounds can exhibit various toxicological effects, including renal, cardiac, and hepatic toxicity. This study aims to investigate the effects of Bidara leaf extract and Java ginseng leaf extract on the macroscopic appearance of the kidneys, heart, and liver of prednisone-induced hypertensive rats. The study used 20 rats divided into five groups: negative control (Na-CMC 1%), positive control (Captopril 25 mg), and three groups receiving combined doses of bidara leaf and Javanese ginseng leaf ethanol extracts (EEBG 50+50 mg/kgBW, EEBG 100+100 mg/kgBW, EEBG 200+200 mg/kgBW). The results showed that the combination extract of Bidara leaves (Ziziphus mauritiana L.) and Ginseng leaves (Talinum paniculatum (Jacq.) Geartn.) at doses of 50+50, 100+100, and 200+200 mg/kgBW did not cause any macroscopic changes. Macroscopic observations showed that the kidneys, hearts, and livers of mice administered EEBG maintained a reddish-brown color with a firm consistency and smooth surface